Mycobacterium tuberculosis Calcium Pump CtpF Modulates the Autophagosome in an mTOR-Dependent Manner - Garg, Rajni; Borbora, Salik Miskat; Bansia, Harsh; Rao, Sandhya; Singh, Prakruti; Verma, Rinkee; Balaji, Kithiganahalli Narayanaswamy; Nagaraja, Valakunja (Frontiers in Cellular and Infection Microbiology, 2020)
Calcium is a very important second messenger, whose concentration in various cellular compartments is under tight regulation. A disturbance in the levels of calcium in these compartments can play havoc in the cell, as it regulates various cellular processes by direct or indirect mechanisms. Here, we have investigated the functional importance of a calcium transporting P2A ATPase, CtpF of Mycobacterium tuberculosis (Mtb) in the pathogen’s interaction with the host. Among its uncanny ways of dealing with the host with umpteen strategies for survival and persistence in humans, CtpF is identified as a new player. The levels of ctpF are upregulated in macrophage stresses like hypoxia, high nitric oxide levels and acidic pH. Using confocal microscopy and fluorimetry, we show that CtpF effluxes calcium in macrophages in early stages of Mtb infection. Downregulation of ctpF expression by conditional knockdown resulted in perturbation of host calcium levels and consequent decreased activation of mTOR. We present a mechanism how calcium efflux by the pathogen inhibits mTOR-dependent autophagy and enhances bacterial survival. Our work highlights how Mtb engages its metal efflux pumps to exploit host autophagic process for its proliferation.